Cystoscopic characteristic findings of interstitial cystitis and clinical implications - Wan-Ru Yu; Yuan-Hong Jiang; Jia-Fong Jhang; Hann-Chorng Kuo (Tzu Chi Medical Journal)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic inflammatory bladder disease of unknown etiology, characterized by bladder pain and frequency urgency symptoms. Based on the cystoscopic findings after hydrodistention under anesthesia, the phenotype of IC/BPS includes no glamerulation, characteristic glomerulation, and with Hunner's lesion. IC is specifically defined if there are characteristic Hunner's lesion appeared in cystoscopy or after hydrodistention. If there are glomerulations without Hunner's lesion, BPS should be considered. The definition of Hunner's lesion and glomerulations differs based on different definition and observations. Currently, there has been no clear description and grading of the glomerulations and Hunner's lesion. Because the classification of IC/BPS has an impact on the treatment strategy and associated with therapeutic outcome, it is unmet to have a clear definition and consensus on the characteristic cystoscopic findings of IC/BPS. This article reviews the literature and presents the figures of Hunner's lesions and description of different mucosal lesions after cystoscopic hydrodistention.